2017
DOI: 10.1177/0143034316682295
|View full text |Cite
|
Sign up to set email alerts
|

How does school climate impact academic achievement? An examination of social identity processes

Abstract: In explaining academic achievement, school climate and social belonging (connectedness, identification) emerge as important variables. However, both constructs are rarely explored in one model. In the current study, a social psychological framework based on the social identity perspective (Turner, Hogg, Oakes, Reicher, & Wetherell, 1987) is introduced that provides a way to integrate these two areas of enquiry. Using this framework, the current study (N ¼ 340 grade 7 and 9 students) investigates: (a) school cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 67 publications
7
78
0
6
Order By: Relevance
“…Many papers were focused on the problematic relationship between the school climate and the pupils' achievements, because the school climate is a crucial factor in for explaining the pupils' achievements and outcomes. [8][9][10] Similar results are possible to be found in older studies 11 examined the relationship between the school climate and the children's academic and social development in elementary school. The results indicated that the overall school climate and the teacherstudents relationship significantly influenced the school adjustment.…”
Section: Introductionsupporting
confidence: 81%
“…Many papers were focused on the problematic relationship between the school climate and the pupils' achievements, because the school climate is a crucial factor in for explaining the pupils' achievements and outcomes. [8][9][10] Similar results are possible to be found in older studies 11 examined the relationship between the school climate and the children's academic and social development in elementary school. The results indicated that the overall school climate and the teacherstudents relationship significantly influenced the school adjustment.…”
Section: Introductionsupporting
confidence: 81%
“…Hamm and Faircloth (2005) found the students who feel at home on campus are more likely to experience academic success. When students feel attached to their school, they receive the emotional and practical benefits that come along with feelings of belonging (Reynolds, Lee, Turner, Bromhead, & Subasic, 2017). Yet, many adolescents do not feel any particular attachment to their school (Hamm & Faircloth, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Scannell and Gifford (2017) suggest that feeling attached to a particular place gives an individual a sense of "comfort and security," both materially and psychologically (p. 261). These psychological benefits correspond to stronger academic performance in school (Reynolds, Lee, Turner, Bromhead, & Subasic, 2017). Feeling "at ease" in a particular place allows an individual to shift his or her attention away from worries or fears (Baumeister & Leary, 1995).…”
Section: Belonging and Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…School climate can also be determined by positive feelings of safety, connectedness, and opportunities for social, emotional, and academic development (Conderman, Walker, Neto, & Kackar-Cam, 2013;De Pedro, Gilreath, & Berkowitz, 2016;Voight, Hanson, O'Malley, & Adekanye, 2015). School environment has been shown to affect attendance, motivation, test scores, risk behavior, bullying, drug and alcohol use, overall well-being, and ultimately academic achievement (De Pedro, et al, 2016;Reynolds, Lee, Turner, Bromhead, & Subasic, 2017). Perception of school environment can have an even greater academic impact on students of color than on White students.…”
Section: Belongingmentioning
confidence: 99%